Prospective Arab teachers' emotions as mirrors to their identities and culture. (October 2019) - Hayik, Rawia; Weiner-Levy, Naomi
Abstract: Grounded in theoretical discourses that underscore the significant role of emotions and cultural context in teacher identity construction, this study invites Arab prospective English teachers in Northern Israel to narrate stories of meaningful experiences that have contributed to shaping their identities. Analysis of the narratives illuminated how coercive power relationships in the educational systems and society stirred powerful emotions that affected their professional identities. While research in the field of emotions and language teacher identity focuses on pedagogical aspects of teaching, this study explores emotions that arise due to sociocultural challenges. Highlights: Prospective Israeli-Arab English teachers narrate stories of experiences that have affected their professional identities. The narratives reveal the effects of cultural factors on shaping their identities. Issues of power, politics and social restrictions on females stirred strong emotions. The strong emotions played a significant role in the process of identity construction. The significance of this study lies in shedding light on emotions that arise due to sociocultural challenges.